ANALYSIS OF UZBEK ARTISTS’ WORKS IN THE HISTORICAL GENRE: CREATING COMPOSITIONS ON THE “SARDOBA” THEME - Davlatova Nilufar Mansurovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article examines the creation of compositions based on the“Sardoba” theme and analyzes the works of Uzbek artists within the historical genre. The study explores artistic techniques, thematic representation, and compositional structure used to depict cultural heritage and historical narratives. By analyzing selected artworks, the research highlights how artists convey historical events, architectural symbols, and emotional depth through visual storytelling. The findings underscore the role of composition, color, perspective, and stylistic choices in enhancing the viewer’s understanding of the “Sardoba” theme and its historical significance.